Safeguarding Malaysian folktale through adventure game - Asmidah Alwi,; Harryizman Harun,; Azliza Othman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Folktale is part of people's culture and heritage that represents the identity of a society. Malaysia is prosperous with folktale, which is traditionally diffused verbally from generation to generation. Inopportunely, this heritage is slowly being forgotten by the younger generations especially by teenagers. The study aims to safeguard local folktale through an adventure game made for teenagers. In the context of the study, Bawang Putih Bawang Merah was selected. The study seeks to discover the adventure game’s elements from the game guideline and from the user (teenagers). Once found, it is a question of how both the elements can be employed to design and develop the folktale adventure game branded as Orkid Emas in the study. Based on the definitive version of the game, it is a question of obtaining the teenagers’ feedback about the game’s design and development and safeguarding aspects. The methods employed in the study are the formal and semi-structured interview, document analysis, flowboarding and prototyping. The results of the study show that both the elements of the adventure game from the guidelines and users were ascertained. The Orkid Emas adventure game was successfully designed and developed using the combination of the elements. At large, positive feedback was obtained from select representing teenagers regarding the Orkid Emas’ design and development, and folktale safeguarding aspects.